Effects of the German Due Diligence Act on Supplier Selection in the Agri-Food Sector - Jürgen von Heyden; Vicco von Bülow; Sarah Iweala; Achim Spiller (German Journal of Agricultural Economics)
Global supply chains in the agri-food sector are at risk of violations of human rights as well as labour and environmental standards. To address these risks, the German Due Diligence Act (LkSG for „Lieferkettensorgfaltspflichtengesetz”) was enacted, mandating corporate human rights, labour and environmental due diligence. Despite its significance, there is limited research on the LkSG’s impact on supplier management. This study aims to provide initial insights into how the LkSG affects supplier selection in the agri-food sector. We conducted qualitative analyses of expert interviews with fifteen company representatives from the German agri-food sector. The findings reveal that companies are confident in maintaining their current supply chains without systematically reducing their supplier base. They perceive the LkSG’s legal requirements primarily as a task for supplier development rather than selection. While there was no significant increase in supplier selection criteria related to human rights and the environment, some companies have given these criteria greater importance. Future suppliers to the German agri-food sector will need to provide more detailed information on human rights and environmental risks. Additionally, companies have become more selective in their choice of certification and verification schemes.